UCP2 silencing restrains leukemia cell proliferation through glutamine metabolic remodeling - Sancerni, Tiphaine; Renoult, Ophélie; Luby, Angèle; Caradeuc, Cédric; Lenoir, Véronique; Croyal, Mikael; Ransy, Céline; Aguilar, Esther; Postic, Catherine; Bertho, Gildas; Dentin, Renaud; Prip-Buus, Carina; et al. (Frontiers in Immunology, 2022)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematologic malignancy derived from early T cell progenitors. Since relapsed T-ALL is associated with a poor prognosis improving initial treatment of patients is essential to avoid resistant selection of T-ALL. During initiation, development, metastasis and even in response to chemotherapy, tumor cells face strong metabolic challenges. In this study, we identify mitochondrial UnCoupling Protein 2 (UCP2) as a tricarboxylic acid (TCA) cycle metabolite transporter controlling glutamine metabolism associated with T-ALL cell proliferation. In T-ALL cell lines, we show that UCP2 expression is controlled by glutamine metabolism and is essential for their proliferation. Our data show that T-ALL cell lines differ in their substrate dependency and their energetic metabolism (glycolysis and oxidative). Thus, while UCP2 silencing decreases cell proliferation in all leukemia cells, it also alters mitochondrial respiration of T-ALL cells relying on glutamine-dependent oxidative metabolism by rewiring their cellular metabolism to glycolysis. In this context, the function of UCP2 in the metabolite export of malate enables appropriate TCA cycle to provide building blocks such as lipids for cell growth and mitochondrial respiration. Therefore, interfering with UCP2 function can be considered as an interesting strategy to decrease metabolic efficiency and proliferation rate of leukemia cells.